Systematic review and meta‐analysis of internet‐delivered interventions providing personalized feedback for weight loss in overweight and obese adults. (7th March 2016) - Sherrington, A.; Newham, J. J; Bell, R.; Adamson, A.; McColl, E.; Araujo‐Soares, V.
Summary: Background: Obesity levels continue to rise annually. Face‐to‐face weight loss consultations have previously identified mixed effectiveness and face high demand with limited resources. Therefore, alternative interventions, such as internet‐delivered interventions, warrant further investigation. The aim was to assess whether internet‐delivered weight loss interventions providing personalized feedback were more effective for weight loss in overweight and obese adults in comparison with control groups receiving no personalized feedback. Method: Nine databases were searched, and 12 studies were identified that met all inclusion criteria. Results: Meta‐analysis, identified participants receiving personalized feedback via internet‐delivered interventions, had 2.13 kg mean difference (SMD) greater weight loss (and BMI change, waist circumference change and 5% weight loss) in comparison with control groups providing no personalized feedback. This was also true for results at 3 and 6‐month time points but not for studies where interventions lasted ≥12 months. Conclusion: This suggests that personalized feedback may be an important behaviour change technique (BCT) to incorporate within internet‐delivered weight loss interventions. However, meta‐analysis results revealed no differences between internet‐delivered weight loss interventions with personalized feedback and control interventions ≥12 months. Further investigation into longer term internet‐delivered interventions is required to examine how weight loss could be maintained. Future research examining which BCTs are most effective for internet‐delivered weight loss interventions is suggested.